BUSINESS ETHICS AND THE INFLUENCE OF VOICE COMMERCE (SMART SPEAKER)-BASED DIGITAL MARKETING ON PURCHASING DECISIONS - Ilham Akbar; Abdi Wijaya (Universitas Kuningan, 2025)
Digital transformation has introduced voice commerce as an innovation in artificial intelligence–based marketing strategies, enabling consumers to interact through voice commands. This study aims to examine the influence of business ethics and voice commerce–based digital marketing on purchase decisions, with consumer trust as a mediating variable. The research employed an explanatory quantitative approach with 250 respondents who use smart speakers in Indonesia. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to evaluate the interrelationships among variables and the strength of mediation. The findings reveal that business ethics significantly and positively influence consumer trust, which subsequently increases purchase decisions. Moreover, voice commerce enhances the emotional connection between users and brands through natural and personalized interactions, although privacy and data security remain key concerns. Consumer trust acts as a crucial mediator linking ethical business practices to purchase decisions. The results confirm that the integration of moral values and digital technology shapes ethical and sustainable consumer behavior. This study concludes that the success of digital marketing in the voice commerce era depends on how well companies uphold fairness, transparency, and social responsibility principles in the use of voice technology. The theoretical contribution lies in the development of the Ethical Voice Commerce Framework, while the practical implication emphasizes the importance of implementing digital ethics governance to enhance consumer trust and loyalty.